OTONOMI DAERAH DAN PENGELOLAAN SUMBERDAYA ALAM : KASUS PENGELOLAAN HUTAN DI SULAWESI SELATAN - Baharuddin Nurkin (Forestry Faculty of Universitas Hasanuddin, 2006)
Decentralization has been regarded as a best way to utilize natural resources for local people benefit and to distribute development results fairly through out of entirely of the country. However, experience has shown that in some cases decentralization in forest management policy was not implemented by local authorities in balancing way of both utilization and conservation. On the other hand, local government complained that even though power transfer to local authority has been implemented since the Indonesian reform politic, central government is still maintaining control over the forest management policy. This article describes decentralization experiences of forest management policy in South Sulawesi. Their impacts followed by some suggestions are also outlined. Key words : Decentralization, Forest management, Local Authority, Central Goverment